2015
DOI: 10.1021/acs.nanolett.5b01381
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons

Abstract: We investigate the phase-dependent excitation of localized surface plasmon polaritons in coupled nanorods by using nonlinear spectroscopy. Our design of a coupled three-nanorod structure allows independent excitation with cross-polarized light. Here, we show that the excitation of a particular plasmon mode can be coherently controlled by changing the relative phase of two orthogonally polarized light fields. Furthermore, we observe a phase relation for the excitation that is dominantly caused by damping effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Similarly, in Ref. [121] it was shown that THG signal emitted from a threenanorod gold structure can be coherently controlled by changing a relative phase of two different excitation channels. Localized surface plasmon polaritons in the nanorods are excited through near-and far-field couplings to two orthogonally polarized light fields.…”
Section: Plasmonic Nanoparticlesmentioning
confidence: 81%
“…Similarly, in Ref. [121] it was shown that THG signal emitted from a threenanorod gold structure can be coherently controlled by changing a relative phase of two different excitation channels. Localized surface plasmon polaritons in the nanorods are excited through near-and far-field couplings to two orthogonally polarized light fields.…”
Section: Plasmonic Nanoparticlesmentioning
confidence: 81%
“…Furthermore, we showed that the modal interplay occurring in the SHG from plasmonic nanostructures may be used to measure small refractive index changes [45][46][47]. These results can also open interesting directions for the dynamic control of harmonic generations in plasmonic nanostructures based on engineering the relative phase between the different modes [50,51].…”
mentioning
confidence: 72%
“…Since the recorded signal depends upon the experimental configuration of the detection, special care is required to determine the nonlinear conversion rate and to design efficient nonlinear plasmonic nanostructures. Furthermore, we showed that the modal interplay occurring in the SHG from plasmonic nanostructures may be used to measure small refractive index changes. These results can also open interesting directions for the dynamic control of harmonic generations in plasmonic nanostructures based on engineering the relative phase between the different modes. , …”
mentioning
confidence: 90%
“…This suggests a departure from conventional physical limitations in nonlinear optics. Metamaterials with tailored nonlinear responses look set to provide exceptional flexibility in applications such as super-resolution imaging 17 , efficient frequency conversion 18 , optical switching and coherent optical control at the nanoscale 19,20 .…”
Section: Supplementary Informationmentioning
confidence: 99%